Review : Aplikasi Fraksinasi Pada Pemisahan Senyawa-Senyawa Bahan Alam - Putri, Peni Oktariyani; Septia Miranti; Mirnawati; Oktriyisa Tantia Mini; Nafach Olya Warasky; Helsy Indarwat; Yolla Rizka Amalia (CV. ITTC INDONESIA, 2025)
Fractionation is an important technique in the separation of secondary metabolites from natural products. This method separates compounds based on differences in polarity, size, or affinity for the stationary phase, resulting in more homogeneous and potentially bioactive fractions. This article reviews various fractionation techniques used to separate compounds from medicinal plant extracts, such as vacuum liquid chromatography (VLC), flash column chromatography, centrifugal chromatography (CLC), and fractionation based on solvents of varying polarity. The studies analyzed demonstrate that appropriate fractionation strategies can produce fractions or isolates with biological activity, including antibacterial, antifungal, antioxidant, and anticancer activities. Therefore, the systematic application of fractionation methods is a crucial step in the development of natural products as drug candidates.